The Power Output and Sprinting Performance of Young Swimmers - Barbosa, Tiago M. (2020)
Submitted by Daniel Marinho (dmarinho@ubi.pt) on 2020-02-11T01:09:57Z No. of bitstreams: 1 54 - barbosa2015.pdf: 202593 bytes, checksum: 0f48f77912cbe4664dffcb128293d2f1 (MD5)